OPTIMASI KOMBINASI HPMC DAN CARBOPOL DALAM FORMULA SEDIAAN GEL HAND SANITIZER EKSTRAK ETANOL BIJI PEPAYA (Carica papaya L.) SERTA UJI AKTIVITAS ANTIBAKTERI TERHADAP Escherichia coli - Christe Mareta Ardika Sari; Disa Andriani; Didik Wahyudi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Papaya seeds (Carica papaya L.) have antibacterial activity because they contain terpenoid, karpain and flavonoid compounds. Flavonoids have OH groups that can damage bacterial cell walls. The dry powder of papaya seeds was extracted by maceration method using 80% ethanol. The purpose of this study was to determine the optimal combination of HPMC and carbopol concentrations in the hand sanitizer gel of papaya seed ethanol extract which can influence the in vitro inhibition of Escherichia coli bacteria. The data analysis used in this study was one way ANOVA and then continued with the Post Hoc Tests. The results of the study obtained a yield of 6.933%. The optimum formula obtained is RUN 8 with a concentration of HPMC: Carbopol (0.25gram: 0.75gram). The results of antibacterial activity against Escherichia coli bacteria obtained an average of 44.25 mm from the two samples. The statistical results obtained stated that there was no significant difference between the concentration of A and ciprofloxacin as a positive control. Keywords: HPMC, Carbopol, papaya seeds (Carica papaya L.), Gel hand sanitizer, Escherichia coli